Problem Analysis of the Low Number of New Student Admissions at Islamic Religious Universities in the Papua Region (Case Study at IAIN Fattahul Muluk Papua) - Dyan Pratiwi (Universitas Sebelas Maret, 2024)
The results of new student admissions that do not meet targets have become a problem faced by the Fattahul Muluk Papua State Islamic Institute (IAIN) in recent years. The small number of students has an impact on the level of performance of lecturers, the amount of non-tax state revenue (PNBP), and campus accreditation. It can threaten the existence of the educational institution. The aim of writing this article is to analyze the causes of the problem of the low number of new student admissions at IAIN Fattahul Muluk Papua. The research method used is qualitative research with a case study approach. The analysis technique was carried out descriptively on data obtained through interviews, observations, and relevant documents during this research. The results of this research indicate that the low number of new student admissions at IAIN Fattahul Muluk Papua is due to: 1. The Jayapura region is not a barometer of education; 2. The coverage area of IAIN Fattahul Muluk Papua is far from areas of Muslim communities; 3. The majority of Muslims in the Papua region are Abangan Muslims or not from the Santri group; 4. The campus location is not strategic. 5. Lack of public transportation facilities; 6. The security of the campus environment is not guaranteed; 7. Inadequate campus facilities; 8. The study programs offered at IAIN Fattahul Muluk are mostly based on Islamic religion; and 9. Competitors offering religious-based and general study programs)